COMPARATIVE STUDY OF TEST RESULTS WITH TRUE TRIAXIAL NONHYDROSTATIC TEST AND TRUE TRIAXIAL HYDROSTATIC TEST ON ROCK SPECIMENT IN LABORATORY - KUSUMA (NIM : 12114046), HARRY
Rock masses in field with actual condition will experience different stresses from any direction. Therefore, a triaxial testing development of True Triaxial Nonhydrostatic test (s2 ≠ s3) is required, and the results will then be compared with the results by True Triaxial Hydrostatic test (s2 = s3). Both of these types of testing will be carried on 95 mm x 95 mm x 95 mm concrete sample by previously testing the physical properties, dynamic properties, and other mechanical properties on similar concrete samples. Both of these types of testing will be approached with two different failure criteria to obtain the value of c (cohesion) and ϕ (internal friction angle). True Triaxial Hydrostatic test will be approached with Mohr-Coulomb failure criteria while True Triaxial Nonhydrostatic test will be approached with Mogi-Coulomb failure criteria. The test results showed that the value of c and ϕ under True Triaxial Nonhydrostatic test were respectively 10.59% and 7.2% higher than under True Triaxial Hydrostatic test. Any parameters that have been obtained from physical properties test, dynamic properties test, and mechanical property test will be used to construct a circular tunnel model with 4 m in radius and 250 m below the surface and this model will be analyzed for its safety factor using the values of c and ϕ from both testing types. The value of c and ϕ under True Triaxial Nonhydrostatic test will generate 14.37% higher safety factor than those generated by the value of c and ϕ under True Triaxial Hydrostatic test.